Invasion 1914 : the Schelieffen Plan to the Battle of the Marne : before the trenches : the first battles of World War I /: the Schelieffen Plan to the Battle of the Marne : before the trenches : the first battles of World War I. (2014) - Senior, Ian
No abstract available